2020
DOI: 10.21203/rs.2.13361/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A three-arm, multicenter, open-label randomized controlled trial of hydroxychloroquine and low-dose prednisone to treat recurrent pregnancy loss in women with undifferentiated connective tissue diseases: Protocol for the immunosuppressant regimens for Living FEtuses (ILIFE) Trial

Abstract: Background: Undifferentiated connective tissue disease (UCTD) is known to induce adverse pregnancy outcomes, and even recurrent spontaneous abortion (RSA) by placental vascular damage and inflammation activation. Anticoagulation can prevent pregnancy morbidities. However, it is unknown whether the addition of immune suppressant to anticoagulation can prevent spontaneous pregnancy loss in UCTD patients. The purpose of this study is to evaluate the efficacy of hydroxychloroquine (HCQ) and low-dose prednisone on … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…Hydroxychloroquine administration for autoimmune-related RPL women who did not gain benefit of the low-dose aspirin and LMWH in previous pregnancies, indicated that hydroxychloroquine was able to significantly increase the live birth rate, gestational age at delivery and the mean birth weight, in comparison to placebo group [164]. There are some ongoing clinical trials assessing the impact of hydroxychloroquine on RPL or RM women [165][166][167]. Nevertheless, the results of a systematic review by Yang et al suggested that combination of hydroxychloroquine with current treatment regimens used in the prevention of RM in APS patients, including low-dose aspirin and heparin, has been shown to have beneficial effects.…”
Section: Hydroxychloroquinementioning
confidence: 99%
“…Hydroxychloroquine administration for autoimmune-related RPL women who did not gain benefit of the low-dose aspirin and LMWH in previous pregnancies, indicated that hydroxychloroquine was able to significantly increase the live birth rate, gestational age at delivery and the mean birth weight, in comparison to placebo group [164]. There are some ongoing clinical trials assessing the impact of hydroxychloroquine on RPL or RM women [165][166][167]. Nevertheless, the results of a systematic review by Yang et al suggested that combination of hydroxychloroquine with current treatment regimens used in the prevention of RM in APS patients, including low-dose aspirin and heparin, has been shown to have beneficial effects.…”
Section: Hydroxychloroquinementioning
confidence: 99%
“…The effectiveness of HCQ in slowing the progression of UCTD to SLE was suggested based on a retrospective analysis [55]. Two RCTs are currently underway to determine the effectiveness of HCQ in MCTD and UCTD [56,57].…”
Section: Mechanizm I Efekty Działaniamentioning
confidence: 99%
“…Skuteczność HCQ w spowolnieniu progresji UCTD do SLE sugerowano na podstawie analizy retrospektywnej [55]. Aktualnie prowadzone są RCT mające na celu potwierdzenie skuteczności HCQ w MCTD i UCTD [56,57].…”
Section: Mechanizm I Efekty Działaniaunclassified